Religious and spiritual experiences - Wildman, Wesley J., 1961- (Cambridge ; New York : Cambridge University Press, 2011)
"What is the value of religious and spiritual experiences within human life? Are we evolutionarily programmed to have such experiences? How will emerging technologies change such experiences in the future? Wesley Wildman addresses these key intellectual questions and more, offering a spiritually evocative naturalist interpretation of the diverse variety of religious and spiritual experiences. He describes these experiences, from the common to the exceptional, and offers innovative classifications for them based on their neurological features and internal qualities. His account avoids reductionalistic oversimplifications and instead synthesizes perspectives from many disciplines, including philosophy and natural sciences, into a compelling account of the meaning and value of religious and spiritual experiences in human life. The resulting interpretation does not assume a supernatural worldview nor does it reject such experiences as positive affirmation of this-worldly existence"--
"What is the value of religious and spiritual experiences within human life? Are we evolutionarily programmed to have such experiences? How will emerging technologies change such experiences in the future? Wesley Wildman addresses these key intellectual questions and more, offering a spiritually evocative naturalist interpretation of the diverse variety of religious and spiritual experiences. He describes these experiences, from the common to the exceptional, and offers innovative classifications of them based on their neurological features and their internal qualities. His account avoids reductionalistic oversimplifications and instead synthesizes perspectives from many disciplines, including philosophy and natural sciences, into a compelling account of the meaning and value of religious and spiritual experiences in human life. The resulting interpretation does not assume a supernatural worldview nor does it reject such experiences as positive affirmation of this-worldly existence"--
Machine generated contents note: Preface; Acknowledgements; 1. Exploring a strange yet familiar landscape: a strategy for interpreting religious and spiritual experiences; 2. Spirituality and the brain: a revolutionary scientific approach to religious and spiritual experiences; 3. A smorgasbord of dangers and delights: the phenomenology of religious and spiritual experiences; 4. Gateway to ultimacy: the importance of intense experiences; 5. Can you trust your instincts? The cognitive reliability of religious and spiritual experiences; 6. The brain-group nexus: the social power of religious and spiritual experiences; 7. Make it start, make it stop! Religious and spiritual experiences in the future; 8. Brains in bodies, persons in groups, and religion in nature: an integrative interpretation of religious and spiritual experiences; Glossary of key terms; Works cited.
Includes bibliographical references (p. 271-299) and index.
Description based on print version record.
Keywords: Experience (Religion); Technology; Electronic books; RELIGION / General